JieZe-1 Alleviates HSV-2 Infection-Induced Genital Herpes in Balb/c Mice by Inhibiting Cell Apoptosis via Inducing Autophagy - Shao, Qingqing; Wu, Fan; Liu, Tong; Wang, Wenjia; Liu, Tianli; Jin, Ximing; Xu, Lijun; Ma, Yonggui; Huang, Guangying; Chen, Zhuo (Frontiers in Pharmacology, 2021)
Objectives: Genital herpes (GH) is a common sexually transmitted disease mainly caused by herpes simplex virus 2 (HSV-2). JieZe-1(JZ-1) is an in-hospital prescription that has been used in Tongji Hospital for many years to treat various lower female genital tract infectious diseases. Our previous study showed that JZ-1 can protect against HSV-2 infection in vitro by inducing autophagy. However, whether JZ-1 can protect against HSV-2 infection in vivo, and the underlying mechanisms involved still remain unclear. Therefore, this study was designed to address above questions. Methods: 8-week-old female balb/c mice were injected intravaginally with HSV-2 to establish GH model. The symptom score, body weight, and histological examination were recorded to assess the animal model of HSV-2 infected and the therapeutic effect of JZ-1. Inflammatory response was determined by detecting inflammatory cells infiltration and local cytokines levels. After then, under autophagy inhibitor chloroquine application, we measured the levels of cell apoptosis and autophagy and investigated the relationship between enhanced autophagy and cell apoptosis. Next, the classic PI3K/Akt/mTOR axis was examined, and in vitro experiment was carried out for further verification. Results: Our results showed that JZ-1 administration significantly reduces symptom score, increases weight gain and alleviates histological damage in HSV-2 infection-induced GH in balb/c mice. JZ-1 administration obviously ameliorates inflammatory responses with reduced T-lymphocytes, T helper cells, macrophages and neutrophils infiltration, and local IL-1β, IL-6, TNF-α and CCL2 levels. HSV-2 infection leads to massive cell apoptosis, which was also restored by JZ-1. Meanwhile, we found that HSV-2 infection blocks autophagic flux in vivo and JZ-1 administration induces autophagy. After chloroquine application, it was observed that the inhibition of autophagy is strongly associated with increased cell apoptosis, whereas the promotion of autophagy remarkedly decreases apoptosis. These results suggested that JZ-1 inhibits cell apoptosis in GH by inducing autophagy, which was further supported in later in vitro experiment. Additionally, PI3K/Akt/mTOR signaling pathway was also downregulated by JZ-1 administration. Conclusion: Our data demonstrated that JZ-1 can alleviate HSV-2 infection-induced GH in balb/c mice by inhibiting cell apoptosis via inducing autophagy, and the underlying mechanisms may be associated with the inhibition of PI3K/Akt/mTOR pathway.